Investigating the Influence of Attitudes and Behaviours of Knowledge Professionals on the Effectiveness of Knowledge Management System: A Study on Turkish Corporations - (:unkn) unknown (My University, 2014)
Bu çalışmanın amacı, bilgi profesyonelleri olarak bilinen bilgi işçilerinin ve bilgi sağlayıcılarının tutum ve davranışları ile bilgi yönetim sürecinin etkinliğinin bilgi yönetim sistemi üzerindeki etkilerini araştırmaktır. Araştırma örneklemini Türkiye'de faaliyette bulunan çeşitli özel şirletlerde çalışan bilgi profesyonelleri (N = 304) oluşturmaktadır. Çalışmada değişkenler arasındaki ilişkiyi analiz etmek için faktör, korelasyon, duncan ve regresyon testleri yapılmıştır. Araştırma bulguları, bilgi profesyonellerinin idari davranışları, tutumları ile bilgi yönetim sistemi üzerinde olumlu etkisini ortaya koyarken, bilgi yönetim sisteminin etkinliği arasında anlamlı bir ilişkiye rastlanmamıştır.

The purpose of this study is to investigate the relationship between attitudes, behaviours of knowledge professionals, and the efficiency of knowledge management process on the effectiveness of knowledge management system in Turkish p rivate sector comp anies. The data were gathered f rom knowledge professionals (N=304) currently employed in different sectors, located in Turkey. The factor, correlation, duncan and regression tests were conducted to analyze the relationship between the variables. The empirical findings indicate that attitudes of knowledge professionals and administrative behaviours of employees have a significant positive effect on effectiveness of knowledge management system. There has been no significant relationship found between the efficiency of process and the effectiveness of the system.
Bilgi Yönetim Sisteminin Etkinliği Üzerinde Bilgi Profesyonellerinin Tutum ve Davranışlarının Etkisinin İncelenmesi: Türk Firmaları Üzerine Bir Araştırma
Keywords: Bilgi, Belge Yönetimi